1980
DOI: 10.2307/2937248
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Relationships among Shrubsteppe Passerine Birds: Competition or Opportunism in a Variable Environment

Abstract: The suggestion that in less stable environments resource limitation and subsequent interspecific competition may be relatively unimportant in determining bird community structure is explored by examining the dietary relationships within a guild of three ground—foraging passerine birds (Horned Lark, Sage Sparrow, and Western Meadowlark) in the shrubsteppe of southeastern Washington, USA, an area of severe, arid, unstable climate. General dietary analyses indicated a strong temporal component to the organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
89
1
5

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 48 publications
5
89
1
5
Order By: Relevance
“…Esta es, precisamente, la tendencia observada en la mayor parte de las especies del ensamble y está reflejada también en el incremento en importancia de los gremios asociados en sentido amplio a la vegetación (tanto en número de gremios como en el de especies dentro de los mismos) durante la primaveraverano. Estos resultados constituyen una evidencia de la importancia de las estrategias oportunistas entre los organismos de las zonas áridas (Wiens y Rotenberry 1979, Rotenberry 1980b, Polis 1991, Boobyer y Hockey 1994) y, a la vez, sugieren que la estructura gremial puede no ser el resultado de procesos organizativos como la competencia interespecífica (Capítulo 1), sino más bien la expresión epifenomenológica , MS) de la existencia de grupos de especies que responden de manera oportunista a las variaciones en la abundancia de distintos recursos (Jaksic et al 1991). Estos aspectos serán abordados en los restantes capítulos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Esta es, precisamente, la tendencia observada en la mayor parte de las especies del ensamble y está reflejada también en el incremento en importancia de los gremios asociados en sentido amplio a la vegetación (tanto en número de gremios como en el de especies dentro de los mismos) durante la primaveraverano. Estos resultados constituyen una evidencia de la importancia de las estrategias oportunistas entre los organismos de las zonas áridas (Wiens y Rotenberry 1979, Rotenberry 1980b, Polis 1991, Boobyer y Hockey 1994) y, a la vez, sugieren que la estructura gremial puede no ser el resultado de procesos organizativos como la competencia interespecífica (Capítulo 1), sino más bien la expresión epifenomenológica , MS) de la existencia de grupos de especies que responden de manera oportunista a las variaciones en la abundancia de distintos recursos (Jaksic et al 1991). Estos aspectos serán abordados en los restantes capítulos.…”
Section: Discussionunclassified
“…En consecuencia, la aproximación depende de la corroboración de una relación entre las características morfológicas de las especies y las características del alimento que consumen (Hespenheide 1971, Wiens y Rotenberry 1980b, Wiens 1984a, Dayan et al 1989, Wainwright 1996, Jones 1997. A pesar de que su importancia es evidente, este supuesto raramente fue considerado y mucho menos puesto a prueba, restringiéndose la mayor parte de los estudios a un examen de las relaciones morfológicas entre las especies (pero véanse Rotenberry 1980b, Wiens y Rotenberry 1980b, Grant 1986b, Jones 1997.…”
Section: Introductionunclassified
“…Kilgo (2005), working in our study site, suggested that arthropod abundance might not be a limiting factor in determining avian habitat selection in some regions or habitat types, and Rotenberry (1980) and Rosenberg et al (1982) concluded that in some situations, the energy demands of birds are small compared to available food resources. In addition, the flexibility of avian foraging strategies (Alatalo 1980, Rotenberry 1980, Hutto 1981) may have allowed birds to adapt to reduced food availability. Because birds are capable of changing both their foraging behavior and the foods they select, they may locate sufficient food without having to leave areas of low insect abundance.…”
Section: Discussionmentioning
confidence: 99%
“…7 Burial Grounds. The dependence of the sage sparrow on sagebrush shrubs (Rotenberry, 1978) for nesting s i t e s limits i t s nesting t o these burial grounds which have a remnant o f sagebrush cover t h a t was not removed during the burial operation. The other three species often s e l e c t nest s i t e s i n areas with l i t t l e or no s h r u b s present (Fitzner, J. N .…”
Section: They Are E S P E C I a L L Y W E L L Adapted T O T H E D R Ymentioning
confidence: 99%
“…The other three species often s e l e c t nest s i t e s i n areas with l i t t l e or no s h r u b s present (Fitzner, J. N . , 1978;Rotenberry, 1978). All other species l i s t e d in Table 19 probably use the burial s i t e s for feeding .…”
Section: They Are E S P E C I a L L Y W E L L Adapted T O T H E D R Ymentioning
confidence: 99%